Quantitative correlation between counterion (X) binding affinity to cationic micelles and X – Induced micellar growth for substituted iodobenzoates (X) - Yusof, N.S.M.; Said, M.N.M.; Khan, M.N. (Elsevier, 2017)
A new semi-empirical kinetic (SEK) method has been used to calculate the values of KX Br or RX Br (X represents substituted iodobenzoates), with KX and KBr representing CTABr micellar binding constants of counterions X− (in the presence of either spherical or non-spherical micelles) and Br− (in the presence of only spherical micelles), respectively. Steady-shear rheological properties of mixed 0.015 M CTABr/[MX] aqueous solutions reveal the presence of flexible wormlike micelles where MX represents sodium 3- and 4-iodobenzoates. The maxima of the plots of viscosity vs. [MX] at 0.015 M CTABr for MX representing sodium 3- and 4-iodobenzoates support the presence of long linear and entangled wormlike micelles.